Assessing and modeling hydrogen reactivity in underground hydrogen storage: A review and models simulating the Lobodice town gas storage - Tremosa, Joachim; Jakobsen, Rasmus; Le Gallo, Yann (Frontiers in Energy Research, 2023)
Underground Hydrogen storage (UHS) is a promising technology for safe storage of large quantities of hydrogen, in daily to seasonal cycles depending on the consumption requirements. The development of UHS requires anticipating hydrogen behavior to prevent any unexpected economic or environmental impact. An open question is the hydrogen reactivity in underground porous media storages. Indeed, there is no consensus on the effects or lack of geochemical reactions in UHS operations because of the strong coupling with the activity of microbes using hydrogen as electron donor during anaerobic reduction reactions. In this work, we apply different geochemical models to abiotic conditions or including the catalytic effect of bacterial activity in methanogenesis, acetogenesis and sulfate-reduction reactions. The models are applied to Lobodice town gas storage (Czech Republic), where a conversion of hydrogen to methane was measured during seasonal gas storage. Under abiotic conditions, no reaction is simulated. When the classical thermodynamic approach for aqueous redox reactions is applied, the simulated reactivity of hydrogen is too high. The proper way to simulate hydrogen reactivity must include a description of the kinetics of the aqueous redox reactions. Two models are applied to simulate the reactions of hydrogen observed at Lobodice gas storage. One modeling the microbial activity by applying energy threshold limitations and another where microbial activity follows a Monod-type rate law. After successfully calibrating the bio-geochemical models for hydrogen reactivity on existing gas storage data and constraining the conditions where microbial activity will inhibit or enhance hydrogen reactivity, we now have a higher confidence in assessing the hydrogen reactivity in future UHS in aquifers or depleted reservoirs.